Resenha de: Bibliography of the Samaritans - Mehlmann, João (Revista de História, 1971)
MAYER (L. A.). — Bibliography of the Samaritans, edited by Donald BROADRIBB (Supplements to Abr-Nahrain, vol. I), E. J. Brill, Leiden 1964, VI + 49 pgs. — fls. 8, 50.